The impact of the use of concept maps in the achievement of the students in the first grade secondary in the southern sector management of education in biology - Al Shehri, Ali Muhammad Abdullah Al Jameel; Al Asmari, Abdullah Nasser Mohammed Al Suroor; Al-Asmari, Muhammad Hizam Mansour (Journal of Educational and Psychological Sciences, 2018)
The objective of the study is to study the effect of using concept maps on the achievement of students in the first grade of secondary education in the southern sector in the management of Nemas. In order to achieve the goal of the research, the researchers used the semi-experimental approach. (120 students). The study tool consisted of tests to measure students’ performance and scores for two groups of students. The test was conducted by teaching the Arthropods group to a group of students. The first sample: (the experimental group) reached 60 students. The method of explaining the teacher using the concept map The second sample: (control group) 60 students The teacher used the usual method of teaching. Companion to examine the hypotheses of the study. The results showed that there was an increase in the average score of direct achievement in favor of the experimental group, which was studied using the concept maps compared with a decrease in the average scores for the direct collection of the control group, and increased interaction and participation by students studying in a method Concept maps. In the light of the results of the study, the researchers recommended using the concept maps and adopting them intensively in the first grade secondary curriculum for biology because there are differences in the average grade of students between the two samples and because the units of the curriculum (biology for the first grade secondary) most of the subjects talk about the classification of living creatures and kingdoms and their sections. Using the Concept Maps Strategy The researchers emphasized that neighborhood teachers need to adopt a concept map strategy for their relevance and relevance to student achievement.